2003
DOI: 10.1007/s00467-003-1197-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone aggravates renal abnormalities induced by neonatal enalapril treatment

Abstract: Lack of neonatal angiotensin II type-1 receptor stimulation produces irreversible abnormalities of renal function and morphology, which can be prevented by simultaneous administration of insulin-like growth factor-I (IGF-I). Given the fact that growth hormone (GH) is the strongest secretagogue for IGF-I, we wanted to explore whether GH could reproduce the effect of IGF-I. Rats were treated from 3 to 13 days of age with the angiotensin-converting enzyme inhibitor enalapril (10 mg/kg/day) and GH (4 mg/kg/day), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition to the direct growth-promoting activity, ANG II may stimulate other growth factors of importance for kidney development. In this regard, we found a decrease in expression of insulin-growth factor-I (IGF-I) and an increase in expression of IGF-binding protein-1, known to suppress IGF-stimulated effects, in the neonatal RAS-inhibited kidneys (Nilsson et al, 2000(Nilsson et al, , 2003. Moreover, the supplementation of IGF-I prevented in part development of renal abnormalities, suggesting a cross-talk between the RAS and IGF-I signalling in postnatal nephrogenesis in the rat (Nilsson et al, 2000).…”
Section: Ang II In Metanephrogenesismentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to the direct growth-promoting activity, ANG II may stimulate other growth factors of importance for kidney development. In this regard, we found a decrease in expression of insulin-growth factor-I (IGF-I) and an increase in expression of IGF-binding protein-1, known to suppress IGF-stimulated effects, in the neonatal RAS-inhibited kidneys (Nilsson et al, 2000(Nilsson et al, , 2003. Moreover, the supplementation of IGF-I prevented in part development of renal abnormalities, suggesting a cross-talk between the RAS and IGF-I signalling in postnatal nephrogenesis in the rat (Nilsson et al, 2000).…”
Section: Ang II In Metanephrogenesismentioning
confidence: 91%
“…2). In this regard, we found a decrease in expression of insulin-growth factor-I (IGF-I) and an increase in expression of IGF-binding protein-1, known to suppress IGF-stimulated effects, in the neonatal RAS-inhibited kidneys (Nilsson et al, 2000(Nilsson et al, , 2003. In addition to the direct growth-promoting activity, ANG II may stimulate other growth factors of importance for kidney development.…”
Section: Ang II In Metanephrogenesismentioning
confidence: 99%
“…In support of this notion, we have demonstrated that neonatal enalapril treatment in rats produces a reduction in insulin‐like growth factor‐I (IGF‐I) mRNA levels specifically in the renal medulla (Nilsson et al. 2000, 2003), as well as an increment in IGF‐binding protein 1 (IGFBP1) mRNA level (Nilsson et al. 2003).…”
Section: Disturbed Renal Growth and Differentiation By Neonatal Ras Bmentioning
confidence: 93%
“…ACE inhibition in neonatal rats leads to an increased renal expression of IGFBP-1 [221] , thereby inhibiting IGF-I action. By adding IGF-I to the ACE inhibition, the animals show normalized renal function and histology [23] .…”
Section: Insulin-like Growth Factor Imentioning
confidence: 99%